When are People Considered “Ahead of Their Time”? Based on the Case Study of Janusz Korczak - Rosemarin, Shoshana (International Journal for Talent Development and Creativity, 2020)
Very rarely is one considered ahead of his/her time. Janusz Korczak has been described by so many as being such a person. His criticism of the educational system in his time served as a motivational force for his innovative pedagogy. His beliefs, techniques and methods have been echoed by experts in special education as well as in gifted education a few decades after his lifetime. The analysis of Korczak’s relevant criticism, as well as his unique ideas is chosen as a prototype for the question raised in the title. A short analysis of the work of Feurstein and Renzulli is provided, both of whom reflect the main principles of Korczak.